INDUSTRIAL GROWTH VOLATILITY IN CAMEROON: DOES FINANCIAL SECTOR DEVELOPMENT MATTER? - Ngimanang, Achamoh Victalice; Nembo, Kedju Robert (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
The objective of this paper was to investigate whether changes in financial sector development affect industrial growth volatility in Cameroon. After exploring the related literature on the issue, time series data for 41 years was used spanning from 1979 to 2020 and ARDL bound test estimation technique employed. Findings showed that changes in financial sector development do not significantly affect volatility in industrial growth in the country. Also, financial sector development as a moderating factor renders changes in inflation volatility insignificant in controlling industrial growth volatility in the economy. The authors recommend that stakeholders should implement policies to bridge the gap separating the financial sector and the industrial sector of the country so that they should be interdependent. The financial sector as well should be empowered to meet the demands of the industrial sector for the industrial sector to principally rely on it for finance.